The politics of rap: Rap music as a tool for expressing exclusion in Istanbul - Mişe, Umut. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
In Istanbul, in the neighborhoods where there are problems such as poverty, discrimination and exclusion with the effect of urbanization, globalization and neoliberalism, young people who suffer from these problems use rap music as an instrument of resistance and as a tool for expressing exclusion. In Sulukule and Bağcılar where the abovementioned problems exist, the young people who socialize around rap music reflect both the reality of these neighborhoods and struggle against social stigmatization and exclusion. In addition, these rappers do not only talk about the local issues, but they also touch upon social inequality, justice and freedom beyond their locality and spatiality. Nevertheless, rappers who try to disseminate their arts through social media, earn money and become famous get more moderate. Especially, the discourse of Bağcılar rappers who prefer to “amateurishly” publish their works on social media unlike Sulukule rappers who make professional album works, becomes more moderate in terms of critique and resistance as the competitive market logic gets dominant.
Keywords: Rap (Music) -- Istanbul.; Neighborhoods -- Social aspects -- Istanbul.